Analysis Of Factors That Influence Employee Performance Through Work Effectiveness - Qristin Violinda; Ika Shofiana; Rr Hawik Ervina Indiworo (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of organizational support and reward systems on employee performance with work effectiveness as an intervening variable. the data analysis technique used in this study was PLS-SEM with a total of 106 employees as respondents. data processing in this study was assisted using smartPLS 3.0. The results of this study indicate that organizational support has no effect on work effectiveness with a P-Value (0.066), the reward system has a positive influence on work effectiveness with a P-Value (0.002), work effectiveness has a positive influence on employee performance with a P value -Value (0.007), organizational support has no effect on employee performance with a P-Value (0.180), the reward system has a positive influence on employee performance with a P-Value (0.000), organizational support has a positive influence on employee performance with P-Value (0.044), the reward system does not have a positive effect on employee performance with a P-Value (0.111)